"The Beaver" as Ideology: Constructing Images of Inuit and Native Life in Post-World War II Canada - Sangster, Joan (Anthropologica, 2022)
This paper explores the Beaver’s use of imagery and text to create an ideology of Canadian "northerness" that promoted ideals of anthropological discovery, historical pride and liberal tolerance for other cultures, while also reinforcing colonial images of Inuit and Native peoples. Although the Beaver was intended as a public relations endeavour by the Hudson’s Bay Company, the magazine gained readership from the 1940s to the 1960s as a National Geographic style publication offering authentic images of the North, Canadian history, white exploration and Native peoples, especially those from the West. By uncovering the recurring images of Inuit and Native in the Beaver we can better understand the dominant ideologies concerning race and Indigenous cultures in this time period, and thus view the cultural terrain upon which political and social decisions concerning First Nations peoples were constructed. Three themes—expert accounts, the historical picturesque, development narratives—are utilized here to explore dominant discourses in the magazine.